Transparency of financial statements prepared under IFRS as an instrument of anti-corruption activity in Ukraine - L.V. Chyzhevska; Y.I. Koretska; A.S. Palamarchuk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Corruption as a social phenomenon leads to a decrease in foreign investment, worsens the economic, political and social situation. As practice shows, measures taken in Ukraine over the last decades, are not sufficiently effective. The level of shadowing of the economy has created an environment for the development of negative phenomena and abuses in the field of accounting. Since January 2016, a Free Trade Zone has been introduced between Ukraine and the EU, and since June 11, 2017, our citizens have been entitled to visa-free entry into the Schengen agreement countries. The full ratification of the Association Agreement is the next logical and strategically important step for Ukraine on the way to the EU. So, domestic businesses will have to get used to European corporate governance, but this guarantees greater protection of the rights of shareholders, creditors and other parties. The signing of the Association Agreement with the European Union has provided Ukraine with a path of change that affects various spheres of state functioning. The scope of accounting and financial reporting is no exception. The question of applying IFRS is a key issue in attracting foreign investment.